Human adipose stem cells induced to osteogenic differentiation by an innovative collagen/hydroxylapatite hybrid scaffold. Issue 10 (19th September 2017) - Mazzoni, Elisa; D'Agostino, Antonio; Manfrini, Marco; Maniero, Stefania; Puozzo, Andrea; Bassi, Elena; Marsico, Stefano; Fortini, Cinzia; Trevisiol, Lorenzo; Patergnani, Simone; Tognon, Mauro
ABSTRACT: Novel biomaterials are of paramount importance for bone regrowth. In this study, we investigated human adipose stem cells (hASCs) for osteogenic, osteoconductivity, and osteoinductivity effects of an innovative collagen/hydroxylapatite hybrid scaffold. In hASCs that were grown on this scaffold, osteogenic genes were analyzed for their expression profiles, together with adhesion and extracellular matrix genes. In hASC integrins, basement membrane constituents and collagens were up‐regulated, together with cell proliferation. In addition, expression of osteopontin and activated focal adhesion kinase was studied at the protein level. Our in vitro data indicate that hASCs, together with hybrid biomaterial, is an important model of study to investigate in vitro bone induction.—Mazzoni, E., D'Agostino, A., Manfrini, M., Maniero, S., Puozzo, A., Bassi, E., Marsico, S., Fortini, C., Trevisiol, L., Patergnani, S., Tognon, M. Human adipose stem cells induced to osteogenic differentiation by an innovative collagen/hydroxylapatite hybrid scaffold. FASEB J. 31, 4555–4565 (2017). www.fasebj.org